USING PERSONAL JOURNAL TO IMPROVE JUNIOR HIGH SCHOOL STUDENTS WRITING SKILL (Karya Ilmiah Mahasiswa (KIMA), 2023)
The objective of the research was to find out the effectiveness of using personal journals and to find out the student's responses to using a personal journal to improve students writing skills. The research design in this research was pre-experimental by using a quantitative method.  The instrument of this research was a test (pre-test and post-test) and a questionnaire. The research consisted of 5 meetings including treatment. The sample of this research was class VIII of 30 students, 26 males, and 14 females. the research of this research indicated that 'the mean score on the pre-test was 51,30 and the mean score of the post-test was 69,53.  It concluded that the rate percentage on the post-test was higher than the rage percentage in the pre-test in teaching writing skills. It was supported by the result of the statistical normality test if the value of significance (2-tailed) < 0.05, then H0 was dejected. And Ha was accepted. On the other hand, if the value of significant (2-tailed) > 0.05, then H0 was accepted, and Ha was dejected. It means that the was a significant improvement in using personal journals. The students responded through a questionnaire researcher concluded that students were responsive and able to improve students learning and writing skills by using a personal journal.